Pengaruh Beban Kerja, Budaya Organisasi, dan Disiplin Kerja terhadap Produktivitas Kerja pada Ud. Berkah Andita Mandiri II - Shahril Sobiri, Muhammad; Zaenul Muttaqien; Agung Pambudi Mahaputra (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the effect of workload, organizational culture, and work discipline on employee productivity at UD. Berkah Andita Mandiri II. In today’s competitive business environment, employee productivity is considered a crucial determinant of organizational performance and sustainability. The research employed a quantitative approach using a survey method by distributing structured questionnaires to employees. A total of respondents participated, and the data collected were processed using multiple linear regression analysis to test both partial and simultaneous influences of the independent variables. The findings reveal that workload has a negative and significant impact on employee productivity, indicating that excessive demands can reduce performance and efficiency. On the other hand, organizational culture and work discipline show positive and significant effects on productivity, suggesting that a strong cultural foundation and consistent discipline practices can enhance employee performance. Moreover, the simultaneous test results confirm that workload, organizational culture, and work discipline collectively have a significant effect on employee productivity. These results emphasize the importance of balancing employee workload to prevent burnout, promoting a positive organizational culture that fosters collaboration and motivation, and consistently enforcing discipline to ensure accountability. Overall, the study highlights that effective human resource management practices play a key role in improving employee productivity and, consequently, in achieving organizational goals.